The Relationship Between Narcissistic Personality and Violent Behavior as Represented in William Golding’s Lord of the Flies - Mahwa Said; Gindho Rizano (English Department, Faculty of Humanities, Andalas University, 2020)
This thesis explores the violent behaviour illustrated in William Golding’s Lord of the Flies. It focuses on the antagonist’s Narcissistic Personality Disorder (NPD) in order to reveal the motives behind his violent behaviour. The writers apply psychoanalytical theory and brings in contemporary theories by experts in psychology in order to help better understand the psychological problems in the novel. The writers conclude that NPD and violent behaviour of the antagonist are ultimate interlinked.